Meconium Stained Amniotic Fluid – A Potential Predictor Of Meconium Aspiration Syndrome - Swain, P; Thapalial, A (Journal of Nepal Paediatric Society, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Objective: To identify potential predictors of Meconium Aspiration Syndrome (MAS) in pregnancies complicated by meconium-stained amniotic fluid (MSAF) & to review the incidence, morbidity and mortality of Meconium Aspiration Syndrome (MAS). Methods: In the period of 2003 to 2006,175 pregnancies with thick meconium-stained AF were delivered; of these, 15 neonates developed MAS and 160 did not. The two groups were compared retrospectively according to maternal findings, pregnancy outcome, and neonatal complications, using univariate analysis (P < 0.05 considered significant) and stepwise multiple logistic regression analysis to identify independent significant factors for prediction of MAS. Results: Incidence of MSAF was 13.97% and that of MAS was 8.57%. All deliveries associated with thick MSAF had developed MAS. 40% mothers were associated with PROM & prolonged labour. Most common & significant risk factors associated with MAS were increased gestational age, increased cesarean section (LSCS) & low Apgar scores at 1 minute and 5 minute. Mortality rate was 6.66% & mechanical ventilation was used in only 1(6.66%) case. Conclusion: MAS are associated with higher incidence of LSCS, lower 1 minute & 5 minute Apgar score & higher gestational weeks. 40% mothers were associated with PROM & prolonged labour. The neonatal morbidity & mortality is significantly more frequent in relation to thick meconium stained amniotic fluid. Specific delivery room resuscitation procedure, early diagnosis & proper management can prevent development of MAS as well as morbidity & mortality. Key words: Meconium Stained Amniotic Fluid, Meconium Aspiration Syndrome and Apgar Score. DOI = 10.3126/jnps.v28i1.1397 J. Nepal Paediatr. Soc. Vol.28(1) p.3-6